2016
DOI: 10.1016/s2213-2600(15)00427-0
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome and critical illness

Abstract: The central role of the microbiome in critical illness is supported by a half century of experimental and clinical study. The physiological effects of critical illness and the clinical interventions of intensive care substantially alter the microbiome. In turn, the microbiome predicts patients’ susceptibility to disease, and manipulation of the microbiome has prevented or modulated critical illness in animal models and clinical trials. This Review surveys the microbial ecology of critically ill patients, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
355
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(367 citation statements)
references
References 168 publications
(217 reference statements)
1
355
0
11
Order By: Relevance
“…The local effects of sepsis, including both microbiome and anatomic disruption, may be contributing factors to recurrent infection at the same site. For example, in critical illness, hypoperfusion and subsequent reperfusion of the intestinal mucosal frequently causes bacterial translocation, and thus a risk factor for recurrent infection(28). Another potential risk factor that should be further investigated is the presence of underlying disease that may predispose patients to developing infection at the same site such as persistent nidus of infection, barrier to infection clearance, or prior indwelling catheters, intravenous lines or invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The local effects of sepsis, including both microbiome and anatomic disruption, may be contributing factors to recurrent infection at the same site. For example, in critical illness, hypoperfusion and subsequent reperfusion of the intestinal mucosal frequently causes bacterial translocation, and thus a risk factor for recurrent infection(28). Another potential risk factor that should be further investigated is the presence of underlying disease that may predispose patients to developing infection at the same site such as persistent nidus of infection, barrier to infection clearance, or prior indwelling catheters, intravenous lines or invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Critical illness and sepsis have a pronounced effect on the gut and lung microbiomes 73 . Conversely, dysbiosis in the gut has been linked to the subsequent hospitalization of patients with sepsis, which suggests an association between the composition of the gut microbiota and sepsis susceptibility 74 .…”
Section: The Microbiome In Sepsismentioning
confidence: 99%
“…A recent manuscript by Zakharkina et al found that duration of mechanical ventilation, but not antibiotic administration, was associated with changes in the respiratory microbiome [15]. Recent studies reported that despite previous evidence [16], highly heterogeneous patterns of intestinal microbiota existed in both septic and non-septic critically ill patients. This might shed light on our understanding of the conflicting results with the effect of probiotics on the incidence of VAP in critically ill patients.…”
Section: Icu-acquired Infectionsmentioning
confidence: 99%